Leadership Ethics Study in Heifetz Perspective and Burns Perspective - Peni Nevia Fitri Ami; Mochammad Isa Anshori (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to explore Heifetz's perspective and Burns' perspective on Leadership Ethics, the dark side of leadership and the principles of ethical leadership. In this study using a literature study approach where the authors rely on various literature to obtain data and use qualitative methods because the data generated is in the form of words or descriptions. The results of this study indicate that the ethical leadership quality of a leader must be improved according to the target in terms of performance with the ethical principles of good leadership such as honesty, fairness, integrity, altruism and loyalty. It can be concluded that leadership ethics plays a very important role in the process of leading a company